Firefighter salivary cortisol responses following rapid heat stress. (August 2022) - Coehoorn, Cory J.; Neary, J. Patrick; Krigolson, Olave E.; Service, Thomas W.; Stuart-Hill, Lynneth A.
Abstract: This research evaluated the impact of rapid heat stress on the rate of salivary cortisol appearance. We hypothesized that rapid heat stress would result in an increased rate of salivary cortisol appearance. Fourteen adult male participants performed an incremental exercise test to a termination criterion (volitional maximum, core temperature = 39.5 °C, or a 2-h time maximum time) with or without firefighting gear in a laboratory with an ambient temperature of 25-26 °C. Salivary cortisol was collected at each 0.5 °C increase in core temperature. We observed a significant increase (p ≤ 0.01) in the rate of cortisol appearance when the subjects were wearing the firefighting gear; no change was observed without firefighting gear. Our results demonstrate that rapid heat stress and the resulting physiological stress cause a rapid increase in the rate of salivary cortisol appearance. Our results also support previous research demonstrating that cortisol is a sensitive strain metric of heat intolerance. Highlights: Rapid heat stress results in an exponential rate of cortisol appearance. The exponential rate of cortisol appearance is related to physiological stress. Regular acute bouts of rapid heat stress could result in long-term consequences.